Assessing the Effect of the Relationship Marketing on the Customers’ Loyalty in the Public and Private Banks of the Qom Province: A Case Study of Public and Private Banks of the Qom Province - Jandaghi, Gholamreza; Omidinia, Somayeh; Matin, Hasan Zarei; Sepahyar, Abolfazl (Journal of Research in Marketing (ISSN: 2292-9355), 2013)
Competition intensity in market places and perceiving the importance of the customers’ retention for organizations has declined them to develop and maintain long-term relations with the costumers. According to marketing scholars, relationship marketing is the best strategy for this purpose. In this article, the relation of relationship marketing factors and the customers’ loyalty, factors priority and the difference of these variables in the public and private banks in the province of Qom has been assessed.Statistical society of the present research consists of 110 customers of a private bank and a public bank in the province of Qom. The medium for data gathering was a questionnaire, and in this research, a statistical society average test and Fridman test have been used to analyze the data, correlation test to study the relation between marketing factors and customers’ loyalty, and the Two-sample T-Test to study the differences among the variables in the two types of public and private banks. And the results obtained by analyzing the data indicate that there is a positive relation between relationship marketing factors and customers’ loyalty. Commitment, trust, communication and conflict handling factors hold the first to fourth priorities in relation to the customers’ loyalty. And also among the research variables in the two types of public and private banks, no meaningful difference could be observed.